Early clinical response to tofacitinib treatment as a predictor of subsequent efficacy: Results from two phase 3 studies of patients with moderate-to-severe plaque psoriasis. (2nd January 2017) - Tan, Huaming; Valdez, Hernan; Griffiths, Chris E.M.; Mrowietz, Ulrich; Tallman, Anna; Wolk, Robert; Gordon, Kenneth
Abstract: Background: The ability to predict response to psoriasis treatments has important implications. Tofacitinib is an oral JAK inhibitor being investigated for psoriasis. Objective: The objective of this study is to identify and validate the clinical predictors of responses in psoriasis patients treated with tofacitinib. Methods: Selected baseline characteristics or early improvement in Psoriasis Area and Severity Index (PASI) in the phase 3 tofacitinib study OPT 1 (NCT01276639) were evaluated as predictors for a clinical response (75% improvement in PASI [PASI75]) at week 16. Predictive ability was assessed by the area-under-the-receiver operating characteristic curve (AUC-ROC). The predictive ability of the identified variables was validated with study OPT 2 (NCT01309737). Results: PASI improvement at weeks 8 and 12 demonstrated good discriminatory abilities to predict PASI75 response at week 16 (AUC-ROC ≥86% and 94%, respectively) in OPT 1. Validation with PASI50 response at week 8 in OPT 2 to predict PASI75 response at week 16 showed that the sensitivity, specificity, PPV, and NPV were 88%, 69%, 80%, and 81%, respectively, in tofacitinib-treated subjects. Conclusion: Achieving a PASI50 response after 8 weeks of treatment with tofacitinib in psoriasis patients appears to be a reliable predictor of achieving a PASI75 response at week 16. Trial registration: clinicaltrials.gov: NCT01276639 and NCT01309737